Mothers of Africa - Boehmer, E; Boehmer, Elleke Deirdre (1991)
﻿ A protean doctrine, claiming cultural pride and demanding self-expression for those who espouse it, nationalism yet casts its defining symbols and reserves its privileges and powers according to gendered criteria. Nationalism, if seen as symbolically constructed, may be interpreted as a gendered discourse in which subjects in history and also in literature are assumed to be male. Especially in the Manichean worlds of colonial and newly post-colonial societies, nationalist narratives - such as those produced at the time of African independence - read as family dramas in which honour and duty are patrilineally bequeathed, and national sons honour iconic mothers. The invisibilities in nationalist discourse, often left obscure in the interests of an ironic 'liberation', may be redressed both through the displacement of dominant subject positions in literature - where 'non-nationals' tell their own fictions - and through the remoulding of inherited tropes and symbolic scenarios. In this way new plots are written into history; nationalist romances give way to literary fictions. An investigation of the status of nationalism as symbolic language of gender, this thesis concentrates first on the inscription of nationalist icons in post-colonial African literature and on the gendered tropic patterns which govern that inscription. Writers considered include Peter Abrahams, Leopold Senghor, Camara Laye, and Ngugi wa Thiong'o. The iconic role of artist as nationalist hero is explored in particular in a discussion of essays and plays by Wole Soyinka. In its latter half, the thesis looks at African women's writing - novels by Flora Nwapa, Buchi Emecheta, Mariama Bâ and Bessie Head - and the work of a second generation of African writers, considering the ways in which this literature has begun to rescript the dramas of nationalism, to redream its visions of wholeness and healing.